The Effect of Distance Learning on The Learning Outcomes - Sri Agustina Kasim; Meyko Panigoro; Sudirman Sudirman (Journal of Economic and Business Education, 2023)
The data in this study were obtained by distributing questionnaires to students, so the data in this study were primary data. In this study, the researcher used a quantitative method with a simple linear regression technique, with the results showing that distance learning during the Covid-19 pandemic had a positive and significant effect on student learning outcomes for integrated social studies subjects in class IX of SMP Negeri 4 Gorontalo City. After doing the normality test and testing the hypothesis using the regression and correlation analysis formula, for the results of this study the regression equation is Y =7,693+〖0,571 _x. In this study, the variable learning outcomes of integrated social studies subjects in class IX State Junior High School 4 Gorontalo City can be explained by distance learning during the Covid-19 pandemic by 40.9%, and for the remaining 59.1% influenced by other variables that are not examined in this study such as student interest in learning, motivation of parents, student learning styles, as well as school environmental factors and students' play environment